1984
DOI: 10.1111/j.1476-5381.1984.tb16233.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduction by phentolamine of the hypotensive effect of methionine enkephalin in anaesthetized rabbits

Abstract: In intact rabbits anaesthetized with pentobarbitone, methionine enkephalin (Met enkephalin, 1−1,000 μg kg−1 i.v.) produced a dose‐dependent bradycardia and hypotension. The bradycardia and hypotension were antagonized by naloxone hydrochloride (1 mg kg−1), but not by naloxone methobromide (1.3 mg kg−1). Phentolamine (1 and 4 mg kg−1 i.v.) blocked both the hypotension and bradycardia produced by Met enkephalin. The inhibitory effect of phentolamine was not due to a simple hypotensive action of this drug per se … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1986
1986
1993
1993

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…[Met]-enkephalin has been shown to produce hypotension in animals (Moore &Dowling, 1980) andHanbauer et al (1982) have demonstrated that in reserpine-treated dogs with catecholamine depletion, splanchnic nerve stimulation produced an increase in the release of adrenal enkephalins with a fall in blood pressure rather than the usual rise. Moreover Eulie & Rhee (1984) showed that in anaesthetized rabbits, [Met]enkephalin potentiated the hypotension induced by nitroprusside. The possibility then arises that endogenously produced [Metlenkephalin could contribute to the hypotensive effect of nitroprusside.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[Met]-enkephalin has been shown to produce hypotension in animals (Moore &Dowling, 1980) andHanbauer et al (1982) have demonstrated that in reserpine-treated dogs with catecholamine depletion, splanchnic nerve stimulation produced an increase in the release of adrenal enkephalins with a fall in blood pressure rather than the usual rise. Moreover Eulie & Rhee (1984) showed that in anaesthetized rabbits, [Met]enkephalin potentiated the hypotension induced by nitroprusside. The possibility then arises that endogenously produced [Metlenkephalin could contribute to the hypotensive effect of nitroprusside.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover Eulie & Rhee (1984) showed that in anaesthetized rabbits, [Met]enkephalin potentiated the hypotension induced by nitroprusside. The possibility then arises that endogenously produced [Metlenkephalin could contribute to the hypotensive effect of nitroprusside.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Opioid peptides have been shown to decrease blood pressure in the pithed rat [Szabo et al, 1986], anes thetized rabbit [Eulie and Rhee, 1984] and conscious dog [Sander et al, 1981]. Further more, endogenous opioid peptides have also been implicated in the modulation of NE release in the rabbit [Schadt and Gaddis, 1985].…”
Section: Introductionmentioning
confidence: 99%